Analysis of Gangway Noise Influence On Interior Noise Of K1 Stainless Steel Train - Dyah, Ainun Purwining; Salim, Alfi Tranggono Agus; Apriyanto, R. Akbar Nur; Nurdiansyah, Rahardian Titus; Hibbanurrohim, Muhammad Ibram; Hakiki, Zahrani Aniela (Jurnal Teknologi, 2024)
Noise is caused by uncontrollable sounds affected by public health problems and listener discomfort. The research problem is the noise from the gangway to the interior noise of the K1 stainless steel train in evaluating comfort on the train. This research aims to analyze the acoustic characteristics of the gangway and the noise insulation of the gangway based on the value of the sound transmission class. The research method is a quantitative experiment the measures the acoustic parameters of the static K1 stainless steel train at a height of 1.2 m from the floor using a microphone that has units of dB. The study results are the transmission loss (TL) value in the gangway 43.3 dB, the FSTC value in the gangway 15, 11, 18, 23, and the STC value from the simulation results 22. The conclusion of the study is the STC value in the gangway from the calculation results and simulation results based on value classification STC in the ASTM E413-16 standard is categorized as low insulation with a low sound of 20-25.